Structural data from lower Dolpo (western Nepal) - Carosi, Rodolfo; Montomoli, Chiara; Visonà, Dario (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 109